De and re-levering betas with risky debt - Marko Volker Krause (Business Research, 2019)
De- and re-levering betas is important to obtain discount rates for assets that are not publicly traded. A de- and re-levering procedure is around for the case of risk-free debt. The procedure for risky debt is much less clear even under very simplifying assumptions. In this paper, I concretize and extend the procedure for de- and re-levering of betas for companies with risky debt. I derive procedures for different assumptions on the taxation of a cancellation of debt (COD) and for different assumptions regarding the distribution of losses on interest and principal payments. With a tax on the COD I obtain known results. However, without taxes on a COD, the distribution of losses on interest and principal payments matters and equations differ markedly for different assumptions on the assignment of losses to interest and principal payments. Furthermore, using a procedure that does not fit the COD treatment is likely to lead to substantial deviations for de- and re-levered betas from their correct values.
Keywords: G12; G31; G32; G33; 650; Default risk; Tax treatment of default; Betas; Leverage